Embolism resistance in stems of herbaceous Brassicaceae and Asteraceae is linked to differences in woodiness and precipitation. (24th December 2018) - Dória, Larissa Chacon; Meijs, Cynthia; Podadera, Diego Sotto; Del Arco, Marcelino; Smets, Erik; Delzon, Sylvain; Lens, Frederic
Abstract: Background and Aims: Plant survival under extreme drought events has been associated with xylem vulnerability to embolism (the disruption of water transport due to air bubbles in conduits). Despite the ecological and economic importance of herbaceous species, studies focusing on hydraulic failure in herbs remain scarce. Here, we assess the vulnerability to embolism and anatomical adaptations in stems of seven herbaceous Brassicaceae species occurring in different vegetation zones of the island of Tenerife, Canary Islands, and merged them with a similar hydraulic–anatomical data set for herbaceous Asteraceae from Tenerife. Methods: Measurements of vulnerability to xylem embolism using the in situ flow centrifuge technique along with light and transmission electron microscope observations were performed in stems of the herbaceous species. We also assessed the link between embolism resistance vs. mean annual precipitation and anatomical stem characters. Key Results: The herbaceous species show a 2-fold variation in stem P 50 from –2.1 MPa to –4.9 MPa. Within Hirschfeldia incana and Sisymbrium orientale, there is also a significant stem P 50 difference between populations growing in contrasting environments. Variation in stem P 50 is mainly explained by mean annual precipitation as well as by the variation in the degree of woodiness (calculated as the proportion of lignified area per total stem area) and to a lesser extent by the thickness of intervessel pit membranes. Moreover, mean annual precipitation explains the total variance in embolism resistance and stem anatomical traits. Conclusions: The degree of woodiness and thickness of intervessel pit membranes are good predictors of embolism resistance in the herbaceous Brassicaceae and Asteraceae species studied. Differences in mean annual precipitation across the sampling sites affect embolism resistance and stem anatomical characters, both being important characters determining survival and distribution of the herbaceous eudicots.